OFFRED AS THE VICTIM OF TOTALITARIANISM IN MARGARET ATWOOD’S THE HANDMAID’S TALE - RIBKA TRANSISKA DEBORANTI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
Abstract This study uses a descriptive qualitative method which focusing on the literary work in the novel and interpretation on the analysis. The main data is taken from the novel The Handmaid’s Tale written by Margaret Atwood. This subject of study focus on the influences of totalitarianism held in the Republic of Gilead and how Offred resists totalitarianism in the novel. In order to analyze the text, this study uses the theory of Totalitarianism by Friedrich and Brzezinski and Hannah Arendt. The result of this analysis depicts the political system of totalitarianism in Gilead influences their societies, especially Offred and the way to resist against the regime. The features of totalitarianism are used to depict the characteristics of totalitarianism that happen in Gilead society. The totalitarianism ideology brings Offred’s action to resist against it. Keywords: Totalitarianism, Resistance, The Handmaid’s Tale.